Four new species of Typhlocharis (baetica group) (Coleoptera: Carabidae: Anillini) from southwestern Iberian Peninsula with notes on their biogeographical and morphological implications. (17th January 2013) - PÉREZ‐GONZÁLEZ, SERGIO; ZABALLOS, JUAN P.
Abstract : Four new species of Typhlocharis (Carabidae: Anillini) are described from the southwest of the Iberian Peninsula, assigned to the baetica species group. T. prima sp.n., T. secunda sp.n. and T. tertia sp.n. (from La Palma del Condado, Huelva, Spain) are syntopic, and T. quarta sp.n. (from Barrancos, Beja, Portugal) is the first species of the group with umbilicate series 4 + 4. They represent, respectively, the southernmost and westernmost distribution data for the group. The baetica group remains well defined and includes ten species. The diagnosis is simplified, with the confirmation that many morphological features characteristic of this group are widespread within the genus. The defining character is the presence of denticles in apical margin of elytra, not associated to the seventh stria or to the elytral suture. The new species provide morphological data that suggest the baetica and silvanoides groups are closely related. Distribution of both groups in the south of the Iberian Peninsula and the presence of morphological characters that are considered plesiomorphic are coherent with the hypothesis of betic‐riffain origin of the genus. They also support the hypothesis of easy alteration of the umbilicate pattern between closely related species and the independent origin of apical denticles in the group compared with those present in other species of the genus. The presence of three well‐differentiated size ranges in syntopic populations suggest ecological diversification to avoid interspecific competition.